Successful treatment of large cavity esophageal disruptions with transluminal washout and endoscopic vacuum therapy: a report of two cases - Leonard T. Walsh; Justin Loloi; Carl E. Manzo; Abraham Mathew; Jennifer Maranki; Charles E. Dye; John M. Levenick; Matthew D. Taylor; Matthew T. Moyer (Therapeutic Advances in Gastrointestinal Endoscopy, 2019)
Acute, high-grade esophageal perforation and postoperative leak after esophagogastrostomy are associated with high morbidity and mortality due to the development of mediastinitis and thoracic contamination. Endoscopic vacuum therapy has proven to be a feasible, safe therapy for management of esophageal wall defects, but with limited success. We describe a retrospective single-center analysis of two patients who underwent endoscopic vacuum therapy for significant esophageal disruptions with a median cross-sectional diameter of 10.7 cm. The technique involved the use of a standard upper video endoscope, nasogastric tube, and vacuum-assisted closure dressing kit, with endoscopic placement of a polyurethane sponge and nasogastric tube assembly into the mediastinal or thoracic cavity. Serial washout and debridement were performed prior to each sponge insertion. Data were collected on indication, size of the cavities, time to intervention, number of procedures, time to resolution, outcomes, and adverse events. Two patients underwent therapy with a mean age of 69.5. The median size of the collections via longest cross-sectional diameter was 10.7 cm. The average number of endoscopic vacuum therapy performed was six and average duration of therapy was 49 days. Complete resolution was achieved in both patients. One patient died 6 weeks later due to severe sepsis from aspiration pneumonia. Endoscopic washout and debridement followed by endoscopic vacuum therapy can be effective for large, even multiple, thoracic and mediastinal contaminations following esophageal perforation and gastroesopagheal anastomotic dehiscence and leaks in appropriately selected patients.